Greenland, Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
11-9 July 26, 1931. Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. On left, Teuflesschloss with glacier and mountains on the north side of it. Photo taken looking west from S.S. Veslekari.